Coordinated beamforming algorithm assisted by receive beamforming vector estimation - Ying HUANG; Gang-ming LV; Shi-hua ZHU (Tongxin xuebao)
A distributed coordinated beamforming optimization scheme with the assistance of receive beamformer esti-mation was proposed for downlink cellular wireless communication systems. By sharing a small amount of information among cooperated base stations(BSs), the proposed algorithm estimates the receive vectors of related users at the BSs based on MVDR criterion, which are then utilized to optimize the design of transmit beamforming vectors. The simula-tion results and analysis show that the proposed distributed scheme can achieve the performance close to that in the cen-tralized scheme with lower overhead and complexity. In addition, a simplified scheme was also proposed which further reduces the system overhead.